STRATEGI WOMEN FOR WOMEN INTERNATIONAL (WFWI) DALAM PEMBERDAYAAN PEREMPUAN DI AFGHANISTAN - Gilang Agung Septiadi (Frequency of International Relations (FETRIAN), 2019)
This research aims to analyze the strategy of Women for Women International (WFWI) in women empowerment in Afghanistan from 2013 until 2017. This research use qualitative method with analytical descriptive technique. There are two concepts used in this research. First is the concept of Liberal Feminism which will explain the discrimination of women in Afghanistan and second is the concept of Development of Non-Governmental Organizations (NGOs) which will explain women's empowerment in Afghanistan by WFWI. The findings of this research are the success of WFWI in empowering women in Afghanistan which is characterized by their life which before they are only have private life, after empowered they have been able to contribute to public life such as health care, education and employment.